The Effect of Financial Incentives on Task Attractiveness and Individual Performance - Ascaryan Rafinda; Timea Gal; Ascariena Rafinda; Putri Purwaningtyas (Faculty of Economics and Business Universitas Jenderal Soedirman, 2021)
The purpose of this paper is to examine the effect of monetary incentives on unattractive task. Pre-test and post-test were conducted to examine the effect of monetary incentives on unattractive task. The data generated from University Student in Indonesia. Total 53 participant follow two stages of the experiment to do the assignment. The first stage to examine individual performance in the assignment without incentives and the second stage is the treatment group. One group with financial incentives while another group without financial incentives. The T-Test was examining to evaluate the difference between pre-test and post test result. The result shows that monetary incentives could not change people perceived of unattractive task become attractive and could not increase individual performance in unattractive task. But people that perceived the assignment as attractive, they improve the performance when there are monetary incentives. This research found that money could not shift people perception on task attractiveness.